A Directory of U.S. Resources on the Rule of Law for the Independent States of the Former Soviet Union - Crocker C. A.; Kampelman M. M.; Bark D. L. (Washington, D.C. United States Institute of Peace Press, 1992)
Today, each of fifteen independent countries that once comprised the Soviet Union are reconstructing their systems of government and society. As they build new systems based on the rule of law, a wide range of American organizations are lending assistance. These U.S.-based resources and initiatives offer technical assistance, conferences and seminars, exchange programs, scholarships and fellowships, grants, interships, or publications on the rule of law.
Keywords: 341